English as a Foreign Language University (EFL) Students’ Perception of Dictionary Use and Training - Charpentier Jiménez, William (2023)
This article examines students’ perceptions of dictionary use and training in English as a Foreign Language (EFL). The needs of English as a foreign language students in terms of specific dictionary types have received little attention. This research was conducted with 48 English as a foreign language students at a public university in Costa Rica over a year. The researcher used a survey (Appendix 1) to collect students’ opinions about the role of the dictionary in their major. Data indicates that: 1) not all dictionary types are known and used by students, 2) students favor the electronic dictionary over the paper dictionary, and 3) dictionary instruction is weak despite its perceived importance by learners. These conclusions are consistent with the literature surveyed. Furthermore, students’ opinions suggest that dictionary instruction and exposure have not been adequately approached in the language educational program. These results should advance new educational policies that promote the systematic and progressive inclusion of dictionary instruction across the study plan.